(untitled) (Biological Sciences - PJSIR, 2022)
The present study was carried out to estimate the composition and length weight relationship of catfish from Nai Gaj, the largest mountain torrent that originates in the Khirthar range. Fish sampling was conducted from January to December 2017. A total of 177 specimens of five catfish species were recorded during the study, including Rita rita (83); Mystus bleekri (55); Wallago attu (25); Ompok pabda (10) and Bagarius bagarius (4). R. rita was found with maximum percentage (47%), while B. bagarius was observed with lowest percentage (1.7%). Calculations of length weight relationship data for R. rita, bleekri and W. attu were done using equations, log w= _2.4+2.22; log L, log w= _2.66+2.22; log L and log w=_3.94+2.76 log L, respectively. Calculated slope of regression "b" values for three species were 2.22, 2.22 and 2.76 which is suggested for the negative allomatric growth pattern, while the correlation between length and weight derived is R2 values for R. rita, M. bleekri and W. attu were strong (0.97, 0.85 and 0.91) is highly significant. As the fish diversity of this area had never been studied before, therefore our study would also provide new information about the bio-diversity of catfishes for the fisheries biologists.